Selective cytotoxicity of self-assembled BODIPY metalla-rectangles: Evidence of p53-Dependent apoptosis via both intrinsic and extrinsic pathways. (September 2020) - Gupta, Gajendra; Das, Abhishek; Panja, Sourav; Ryu, Ji Yeon; Lee, Junseong; Mandal, Nripendranath; Lee, Chang Yeon
Abstract: The use of florescent ligands in the synthesis of metal based complexes has several advantages for sub-cellular localization studies. However, very few metal macrocycles with luminescent properties have been studied in detail to date. To understand its mechanism of action in detail, a series of novel Ru(II) and Ir(III) BODIPY based metal macrocycles bearing a quinone clip was designed. The reaction between [Ru2 ( p-cymene )2 (dhaq)Cl2 ] or [Ir2 ( Cp* )2 (dhaq)Cl2 ] (dhaq = 1, 4-dihydroxyanthraquinone) and AgCF3 SO3 followed by the addition of different substituted BODIPYR ligands (R = CH3, PhCF3, Ph; BODIPY = boron-dipyrromethene) in methanol formed six novel cationic tetranuclear metalla-rectangles [Ru4 ( p-cymene )4 (BODIPYR)2 (dhaq)2 ] 4+ (R = CH3, 1 ; PhCF3, 2 ; Ph = 3 ) and [Ir4 ( Cp* )4 (BODIPYR)2 (dhaq)2 ] 4+ (R = CH3, 4 ; PhCF3, 5 ; Ph = 6 ). These tetracationic products were isolated in good yields and fully characterized using different analytical techniques including a single crystal X-ray structure. The X-ray structure of rectangle 6 confirmed that two dhaq metal clips were bridged with two BODIPY ligands to form the desired rectangular structure. The biological activity of all prepared rectangles and free ligands were tested in different cancer cell lines and their efficacies were compared with that of the well-known drug cisplatin. The complexes potentially inhibited the proliferation and manipulated the cytokinetics of cancer cells in vitro . The intracellular fates of the compounds were easily visualized by virtue of the various fluorescent BODIPY ligands within the respective complexes. The mechanism of action at a translational level was further examined by measuring the expression of pro- and anti-apoptotic proteins in the treated cancer cells using Western Blotting. Increased Bax/Bcl-2 expression ratio, proteolytic cleavage of various caspases, PARP and Bid, as well as time-dependent upregulation of p53 and apaf-1 showed that the compound induces both the apoptotic pathways in a p53 dependent manner. Highlights: Synthesis and characterization of new BODIPY-based Ru and Ir metalla-rectangles are reported. Physical and biological properties are studied in detail. The complexes potentially inhibited the proliferation and manipulated the cytokinetics of cancer cells in vitro. Mechanism of action at a translational level was examined by measuring the expression of pro- and anti-apoptotic proteins.